2016
DOI: 10.1038/ncomms11794
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing lithium metal using ionic liquids for long-lived batteries

Abstract: Suppressing dendrite formation at lithium metal anodes during cycling is critical for the implementation of future lithium metal-based battery technology. Here we report that it can be achieved via the facile process of immersing the electrodes in ionic liquid electrolytes for a period of time before battery assembly. This creates a durable and lithium ion-permeable solid–electrolyte interphase that allows safe charge–discharge cycling of commercially applicable Li|electrolyte|LiFePO4 batteries for 1,000 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
299
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(313 citation statements)
references
References 49 publications
(57 reference statements)
12
299
1
1
Order By: Relevance
“…15 As such, there have been an increasing number of reports comparing Li symmetric cell data. 3,12,1618 However, a detailed understanding of Li–Li symmetric cells is lacking, due to the complex time-dependent interplay between morphology and electrochemistry occurring at both electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…15 As such, there have been an increasing number of reports comparing Li symmetric cell data. 3,12,1618 However, a detailed understanding of Li–Li symmetric cells is lacking, due to the complex time-dependent interplay between morphology and electrochemistry occurring at both electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has shown that pre-treatment of the Li metal in ionic liquids containing an appropriate lithium salt can effectively supress the formation of the Li metal dendrite during charge-discharge cycling. 321 Typical results from this study are presented in Fig. 35 which plots the discharge capacity and coulombic efficiency of several "Li(─)|Li-salt + ionic liquid|LiFePO4(+)" cells against the charge-discharge cycle number at a rate of 1 C. The low viscosity ionic liquid used in the cell was N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide, [C3mPyr + ][FSI ─ ].…”
Section: Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Tremendous attempts have been tried to mitigate uncontrolled lithium dendrites, mainly including: (i) improving the interface properties between electrode and electrolyte; (ii) constructing lithium‐based composites with 3D hosts. To improve the interface properties, various strategies are proposed and explored, including prefabricating artificial SEI films, precoating chemically inert protective layers, inducing additives in the electrolyte to amend SEI films, and even developing solid‐state electrolyte . Meanwhile, comparing to these attempts on stabilizing lithium anode surface, efforts on constructing lithium‐based composites with 3D hosts are superior on the reduction of local current density and bulk effect during cycling.…”
mentioning
confidence: 99%